THERMODYNAMIC STABILITY ANALYSIS OF THE CARBON BIOGEOCHEMICAL CYCLE IN AQUATIC SHALLOW ENVIRONMENTS - Lvov S.N.; Pastres R.; Marcomini A. (My University, 1996)
We carry out the thermodynamic stability analysis of the carbon cycle in a lagoon. Our approach differs from linear stability analysis, and is based on the excess entropy production. The coupled biogeochemical processes in the lagoon include gas transfer, photosynthesis, respiration, decomposition, sedimentation, and oxidation of algae. The thermodynamic stability criterion derived from this analysis indicates that, in addition to known limiting factors of biomass production such as temperature, light, and nitrogen and phosphorous concentrations, the rate of carbon dioxide delivery from the air reservoir to the water can be also a limiting factor. For the Venice lagoon, the criterion obtained predicts that a doubling of the CO2 partial pressure in the atmosphere can render the system unstable, driving it to dramatic biomass production and degradation.